Bi-FoRe: an efficient bidirectional knockin strategy to generate pairwise conditional alleles with fluorescent indicators. Issue 1 (17th July 2020) - Han, Bingzhou; Zhang, Yage; Bi, Xuetong; Zhou, Yang; Krueger, Christopher J; Hu, Xinli; Zhu, Zuoyan; Tong, Xiangjun; Zhang, Bo
Abstract: Gene expression labeling and conditional manipulation of gene function are important for elaborate dissection of gene function. However, contemporary generation of pairwise dual-function knockin alleles to achieve both conditional and geno-tagging effects with a single donor has not been reported. Here we first developed a strategy based on a flipping donor named FoRe to generate conditional knockout alleles coupled with fluorescent allele-labeling through NHEJ-mediated unidirectional targeted insertion in zebrafish facilitated by the CRISPR/Cas system. We demonstrated the feasibility of this strategy at sox10 and isl1 loci, and successfully achieved Cre-induced conditional knockout of target gene function and simultaneous switch of the fluorescent reporter, allowing generation of genetic mosaics for lineage tracing. We then improved the donor design enabling efficient one-step bidirectional knockin to generate paired positive and negative conditional alleles, both tagged with two different fluorescent reporters. By introducing Cre recombinase, these alleles could be used to achieve both conditional knockout and conditional gene restoration in parallel; furthermore, differential fluorescent labeling of the positive and negative alleles enables simple, early and efficient real-time discrimination of individual live embryos bearing different genotypes prior to the emergence of morphologically visible phenotypes. We named our improved donor as Bi-FoRe and demonstrated its feasibility at the sox10 locus. Furthermore, we eliminated the undesirable bacterial backbone in the donor using minicircle DNA technology. Our system could easily be expanded for other applications or to other organisms, and coupling fluorescent labeling of gene expression and conditional manipulation of gene function will provide unique opportunities to fully reveal the power of emerging single-cell sequencing technologies.